Pengembangan Modul Ajar Pengajuan dan Pemecahan Masalah Matematis untuk Meningkatkan Kemampuan Berpikir Kritis dan Kreatif Siswa - Kurniawan Cahyanto; Tatag Yuli Eko Siswono; Ardi Dwi Susandi (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study aims to develop a teaching module focused on mathematical problem posing and problem solving, specifically within the topic of statistics. The goal is to create a module that is not only valid, practical, and effective but also capable of honing the critical and creative thinking skills of high school students. This study utilizes the Research and Development (R&D) method following the 4D development model. The subjects of this research were 10th-grade high school students. The research findings indicate that the teaching module is considered highly valid, with a score of 4.13. In terms of practicality, it achieved a score of 3.8, suggesting the module is user-friendly, engaging, and supportive of a smooth learning process. The module proved effective in improving students' critical and creative thinking skills, as evidenced by a 42% increase in average test scores after using the module. This research suggests that the developed teaching module is feasible for use as instructional material at the high school level and is capable of strengthening students' critical and creative thinking abilities. This module serves as an alternative instructional resource that encourages active, innovative mathematics learning oriented toward the development of high-order thinking skills (HOTS).